A survey of speech–language therapy provision for people with post‐stroke dysarthria in the UK. Issue 6 (16th June 2017) - Miller, Nick; Bloch, Steven
Abstract: Background: A large number of people who experience a stroke are affected by dysarthria. This may be in isolation or in association with aphasia and/or dysphagia. Despite evidence highlighting the psychological and social impact of having post‐stroke dysarthria and a number of clinical guidelines that make recommendations for appropriate management, little is known currently about UK service delivery issues relating to speech and language therapy (SLT) assessment and treatment for this group. Such evidence is necessary in order to plan, develop and research services for people with post‐stroke dysarthria. Aims: To gain an overview of SLT practices in the management of people with dysarthria after stroke in the UK. Methods & Procedures: SLTs in the UK were asked to complete an online survey addressing referral patterns, caseload profiles, and their assessment and intervention methods for post‐stroke dysarthria. In the absence of a national register of clinicians working with people with acquired dysarthria, a snowballing method was used to facilitate participant recruitment. Results were analysed using descriptive statistics. Outcomes & Results: A total of 146 SLTs responded. The majority were employed by the National Health Service (NHS). Most patients were referred within 1 week post‐stroke. Almost half the respondents did not regularly use formal assessments and the use of instrumentation was rare, including the use of video recording. The focus of therapy for mild, moderate and severe dysarthria did not differ significantly for clinicians. A little under half the respondents endorsed non‐verbal oral exercises in rehabilitation. The survey demonstrated some appreciation of the centrality of regular intensive practice to effect change, but this was in a minority. Conclusions & Implications: Through this research it became clear that basic information regarding post‐stroke dysarthria incidence, prevalence and core demographics is currently unavailable. More embedded NHS SLT reporting systems would make a significant contribution to this area. A more in‐depth examination is required of the natural history of dysarthria over the months and years following stroke, of SLT practices in relation to post‐stroke dysarthria, with investigations to understand more fully the choices SLTs make and how this relates to available evidence to support their clinical decision‐making.